"(It) Shouldn't Be Funny But You Can't Help But Laugh": Black Twitter, #TweetLikeThe1600s, and Black Humor Online1. (June 2022) - Taylor, Zari
In May 2014, comedian Leslie Jones faced backlash after making a joke about slavery during an episode of Saturday Night Live. During the "Weekend Update" sketch of the show, Jones, a Black woman, emphasized that although she was single now, she would have been a hot commodity during slavery. She added that after being hooked up with "the best brother on the plantation" by her massa, she would be popping out "superbabies" every 9 months. Although the show is known for testing the limits of comedy and poking fun at everything, Jones was criticized for making light of such a serious topic. In early 2018, however, Black Twitter picked up right where Jones left off and slavery became a topic of amusement online. Using words, gifs, memes, and videos, users reimagined the lives of enslaved African Americans during the 1600s in a comical manner. This online exchange was marked by the #TweetLikeThe1600s hashtag and went in a series of directions. In what follows, I locate the hashtag in a longer tradition of Black humor as well as analyze subsequent discussions about who is allowed in on the joke. Beyond the jokes themselves, these smaller and supplementary discourses inform my engagement with the subject.